ANALISIS FRAMING PEMBERITAAN SILUET PINOKIO JOKOWI PADA MEDIA ONLINE DETIK.COM DAN SUARA.COM - Noval Setiawan (Mediakita, 2021)
This study aims to explain how online media framing sees an event being reported. And how is the influence of media ownership on online media behavior to keep a neutral and objective position on their news. The object of research is the coverage of "Pinocchio Jokowi Silhouette" on the cover of the 16-22 September 2019 edition of the Tempo Magazine in online media Detik.com and Suara.com. The research method used is a qualitative approach using the Zhong Pan and Geral M. Kosichi framing analysis method. The results showed that the framing of the two media were very different in their presentation. Detik.com framed the news on Siluet Pinocchio Jokowi which seemed less objective and tended to use a single response from the editor of Tempo Magazine and did not pay attention to the balance aspect in the selection of news sources, and showed an attitude of denial of Jokowi's insults. Meanwhile, Suara.com, in its framing, tends to be more objective because it considers other aspects that are more memorable to produce information that is in accordance with its social reality. There were also responses from several figures as sources who had no connection with Tempo Magazine. Although the next announcement, Suara.com was considered insulting Jokowi, which ended with Suara.com reporting to the Press Council.